Association between air quality index and effects on emergency department visits for acute respiratory and cardiovascular diseases. - Panumas Surit; Wachira Wongtanasarasin; Chiraphat Boonnag; Borwon Wittayachamnankul (PLoS ONE, 2023)
Background and objective Several studies suggest that air pollution, particularly PM2.5, increases morbidity and mortality, Emergency Department (ED) visits, and hospitalizations for acute respiratory and cardiovascular diseases. However, no prior study in Southeastern Asia (SEA) has examined the effects of air pollutants on ED visits and health outcomes. This study focused on the association of the Air Quality Index (AQI) of PM2.5 and other pollutants' effects on ED visits, hospitalization, and unexpected deaths due to acute respiratory disease, acute coronary syndrome (ACS), acute heart failure (AHF), and stroke. Methods We conducted a retrospective study with daily data from ED visits between 2018 and 2019 at Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand. The AQI of air pollution data was collected from outdoor air quality from the Smoke Haze Integrated Research Unit and the Air Quality Index Visual Map. A distributed lag, non-linear and quasi-Poisson models were used to explore the relationship between air quality parameters and ED visits for each disease. Results 3,540 ED visits were recorded during the study period. The mean daily AQI of PM2.5 was 89.0 ± 40.2. We observed associations between AQI of PM2.5 and the ED visits due to ACS on the following day (RR = 1.023, 95% confidence interval [CI]: 1.002-1.044) and two days after exposure (RR = 1.026, 95% CI: 1.005-1.047). Also, subgroup analysis revealed the association between AQI of PM2.5 and the ED visits due to pneumonia on the current day (RR = 1.071, 95% CI: 1.025-1.118) and on the following day after exposure (RR = 1.024, 95% CI: 1.003-1.046). AQI of PM2.5 associated with increased mortality resulted from ACS on lag day 3 (OR = 1.36, 95% CI: 1.08-1.73). The AQI of PM10 is also associated with increased ED visits due to COPD/asthma and increased hospitalization in AHF. In addition, the AQI of O3 and AQI of NO2 is associated with increased ICU admissions and mortality in AHF. Conclusion Short-term PM2.5 exposure escalates ED visits for ACS and pneumonia. PM10's AQI associates with COPD/asthma ED visits and AHF hospitalizations. AQI of O3 and NO2's link to increased ICU admissions and AHF mortality. Urgent action against air pollution is vital to safeguard public health.